Modeling of Precipitation Polymerization I: The Method of Finite Molecular Weight Moments - Bouhendi, H.; Haddadi-Asl, V.; Rafizadeh, M.; Safinejad, A. (e-Polymers, 2007)
Precipitation polymerization method is a non homogeneous method in which polymer chains are separated from continuous phase as polymer particles. In this method, all polymerization reactions occur in continuous and polymer dispersed phases based on simultaneous polymerization theory. Hunkeler theory is a perfect "simultaneous polymerization" theory that predicts molecular weights and the rate of polymerization for precipitation polymerization of hydrophilic monomers. In this paper, finite moment method is used to predict features of precipitation polymerization. This model is able to predict number and weight average degree of polymerization in dispersed and continuous phases, polydispersity index (PDI) for two phases and volume fraction of primary and secondary particles. Experimental results are in agreement with the properties of dispersed phase; weight and number average degree of polymerization in the dispersed phase is more than that of degrees of polymerization in the continuous phase. The PDI of polymer formed in the dispersed phase is equal to 2 and that of PDI in the continuous phase is less than 2. Furthermore Hunkeler mathematical model is reviewed critically.